2021
DOI: 10.1111/jcmm.17062
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic machine perfusion attenuates hepatic ischaemia‐reperfusion injury by inhibiting CIRP‐mediated oxidative stress and mitochondrial fission

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…29,30 We showed that this customized setup can reduce IRI in the graft immediately after liver transplantation/reperfusion, measured by tissue injury evaluation and transaminase release. Other authors have shown similar results 31 of NMP on decreased oxidative stress, but this is the first time that IRI was scored in the graft after portal reperfusion, resembling the clinical scenario. Interestingly, this effect did not correlate with lower oxidation in liver tissue measured by MDA in our setup, perhaps due to hyper-oxygenation during NMP.…”
Section: F I G U R E 3 Nmp Summary Results Representation Of Arterial...supporting
confidence: 73%
“…29,30 We showed that this customized setup can reduce IRI in the graft immediately after liver transplantation/reperfusion, measured by tissue injury evaluation and transaminase release. Other authors have shown similar results 31 of NMP on decreased oxidative stress, but this is the first time that IRI was scored in the graft after portal reperfusion, resembling the clinical scenario. Interestingly, this effect did not correlate with lower oxidation in liver tissue measured by MDA in our setup, perhaps due to hyper-oxygenation during NMP.…”
Section: F I G U R E 3 Nmp Summary Results Representation Of Arterial...supporting
confidence: 73%
“…A European single‐center study reported similar findings, with successful transplantation of up to 83% eNMP‐preserved livers that had initially been discarded 17,20 . However, these studies invariably suffered from selection bias, and the true contribution of eNMP to the increased organ utilization rate therefore remains obscure 30,31 . Although derived from non‐randomized trials, cumulative evidence for the value of NRP in DCD liver transplantation suggests that outcomes are improved with respect to IC (Table 3).…”
Section: What Do We Know About Dynamic Preservation?mentioning
confidence: 84%
“… 18 Surprisingly, to date, mechanistic studies dissecting the role of oxygen tension as a driver of mitochondrial injury at normothermic temperatures are unavailable. Nevertheless, metabolomics data from porcine and rat experiments of DCD liver transplantation suggest that NMP can reverse mitochondrial ischemic injury and restore mitochondrial function 30,31 …”
Section: How Does Dynamic Preservation Work?mentioning
confidence: 99%
See 2 more Smart Citations